Problematic internet use and its relationship with eating disorders - Ruiz-Centeno, Claudia; Cueto-Galán, Raquel; Pena-Andreu, Jose Miguel; Fontalba-Navas, Andrés (Frontiers in Public Health, 2025)
Problematic Internet use has been associated with eating disorders. An increasing number of young adults are using social media, and a variety of content promoting anorexia and bulimia (pro-anorexia and pro-bulimia) has been identified. The aim of this study is to qualitatively analyze this content to understand how it affects individuals with eating disorders or those at risk. Content selection was carried out through non-random intentional sampling and based on the following criteria: the most prominent content on each platform in terms of the number of interactions, created within less than 5 years old, and displaying pro-ana and/or pro-mia content in English or Spanish. In total, 6 digital platforms were analyzed, including 57 resources (videos, images, blog entries, chat messages, PDF files, and group descriptions). The discourse was analyzed using both quantitative and qualitative approaches. The analyzed content includes numerous tips and tricks promoting eating disorders. Additionally, a widespread positive sentiment towards low weight and thinness was observed, while negative sentiments were associated with eating, gaining weight, etc. It has been demonstrated that self-esteem in adolescents and young adults can be affected by social media use, leading to body dissatisfaction that may result in increased use of these platforms with access to pro-anorexia and pro-bulimia content, which can contribute to the development of these disorders. The continuous variation and removal of this content, and the health problems it poses, requires further study of these digital resources and how users access them, in order to establish preventive measures to ensure health in the future.